Correlation between AV synchrony and device collected AM‐VP sequence counter in atrioventricular synchronous leadless pacemakers: A real‐world assessment. (15th November 2022) - Garweg, Christophe; Piccini, Jonathan P.; Epstein, Laurence M.; Frazier‐Mills, Camille; Chinitz, Larry A.; Steinwender, Clemens; Stromberg, Kurt; Sheldon, Todd; Fagan, Dedra H.; El‐Chami, Mikhael F.
Abstract: Introduction: Micra atrioventricular (AV) provides leadless atrioventricular synchronous pacing by sensing atrial contraction (A4 signal). Real‐world operation and reliability of AV synchrony (AVS) assessment using device data have not been described. The purposes of this study were to (1) assess the correlation between AVS and atrial mechanical sensed‐ventricular pacing (AM‐VP) percentages in patients with permanent high‐degree AV block and (2) report on the real‐world effectiveness of Micra AV. Methods: The correlation between ECG‐determined AVS in‐clinic and device‐collected %AM‐VP was assessed using data from 40 patients with high‐degree AV block enrolled in the Micra Atrial tRacking using a Ventricular AccELerometer (MARVEL) 2 study. A retrospective analysis to assess continuously‐sampled %AM‐VP since last session, device programming, and electrical parameters was performed using Micra AV transmissions from the Medtronic CareLink database. Patients with transmissions ≥180 days postimplant were included. Results: Among the 40 MARVEL 2 AV block patients with a median %VP of 99.7%, AVS was highly correlated with AM‐VP (median AVS 87.1%, median AM‐VP 79.1%; R 2 = 0.764, p < .001). The CareLink cohort included 4384 patients programmed to VDD mode. The mean A4 amplitude was 2.3 ± 1.8 m/s 2 at implant and 2.3 ± 1.6 m/s 2 at 28 weeks. In patients with %VP >90% ( n = 1662), the median %AM‐VP was 74.7%. For the full cohort, median %VP was 65.6% and median projected battery longevity was 10.5 years. Conclusion: In patients with a high pacing burden, %AM‐VP provides a reasonable estimation of AVS. The first large real‐world analysis of Micra AV patients with >90% VP showed stable atrial sensing over time with a median %AM‐VP, a correlate of AVS, of 74.7%.